The influence of Rose Bengal photosensitizer on the productivity and pigment composition of Haematococcus pluvialis - Pechenkina, Elizaveta I.; Samovich, Tatyana V.; Kozel, Nikolay V. (Experimental Biology and Biotechnology, 2021)
The stimulation of astaxanthin synthesis in Haematococcus pluvialis cells under high-intensity light in the combined action of Rose Bengal photosensitizer has been established. It was revealed that when Rose Bengal was used as an additional inducer of carotenogenesis in high-intensity light, the dry weight of the Haematococcus and the diameter of the cells in suspension increase compared to the action of only high-intensity light on algae cells. The observed increases in dry weight are significant and reach 40 % excess over control. We suggest that the increase in dry weight, Haematococcus cell diameter and astaxanthin yield when H. pluvialis photosensitizer is added to the incubation medium against the background of high-intensity light is not associated with increased stress (since the used concentrations of Rose Bengal are too small to induce photo-oxidative stress), but the signaling properties of the generated Rose Bengal singlet oxygen, which may be the primary agent in the transduction of a signal that triggers increased synthesis of astaxanthin in H. pluvialis cells.